2001
DOI: 10.1063/1.1428120
|View full text |Cite
|
Sign up to set email alerts
|

High-performance photorefractive polymer composite with 2-dicyanomethylen-3-cyano-2,5-dihydrofuran chromophore

Abstract: A nonlinear optical chromophore for photorefractive applications containing a 2-dicyanomethylen- 3-cyano-2,5-dihydrofuran acceptor group is presented. When doped into a plasticized composite of poly(n-vinylcarbazole), large gain coefficients (Γ) are observed with photorefractive speed similar to the best composites reported in the literature while maintaining low sample absorption (∼15 cm−1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…[1] In PR materials, charges photogenerated by a nonuniform lightintensity pattern are transported and redistributed in space to produce an internal space-charge electric field, which, in turn, modulates the refractive index via molecular reorientations and electro-optic (EO) effects. Because of their potential applications in holographic optical data storage and real-time optical processing, various classes of organic PR materials, including polymers, [2][3][4] liquid crystals, [5] and organic glasses, [6][7][8] have been explored. Of these, organic molecular glasses are considered very promising since they possess many advantages, such as a simple synthetic approach, a well-defined molecular structure, long-term stability with high chromophore concentration, and the best PR performance.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In PR materials, charges photogenerated by a nonuniform lightintensity pattern are transported and redistributed in space to produce an internal space-charge electric field, which, in turn, modulates the refractive index via molecular reorientations and electro-optic (EO) effects. Because of their potential applications in holographic optical data storage and real-time optical processing, various classes of organic PR materials, including polymers, [2][3][4] liquid crystals, [5] and organic glasses, [6][7][8] have been explored. Of these, organic molecular glasses are considered very promising since they possess many advantages, such as a simple synthetic approach, a well-defined molecular structure, long-term stability with high chromophore concentration, and the best PR performance.…”
Section: Introductionmentioning
confidence: 99%
“…[11±19] The best PR polymer composites are characterized by millisecond-response times, [20] two-beam coupling gain coefficients of % 400 cm À1 , [21] and diffraction efficiencies of % 100 % [22] at applied electric fields of % 100 V mm…”
Section: Introductionmentioning
confidence: 99%
“…These molecules contain an amine donor and a dicyanodihydrofuran (DCDHF) acceptor linked by a conjugated unit (benzene, thiophene, alkene, styrene, etc.) and were originally designed to deliver both high polarizability anisotropy and dipole moment as nonlinear optical chromophores for photorefractive applications 21,22 . Surprisingly, we have found that these molecules are also well-suited for single-molecule fluorescence applications.…”
Section: Introductionmentioning
confidence: 99%